Serum glucose and fructosamine levels as possible indicators of diabetes mellitus in dogs - Morales Hernández, Luisa Fernanda (2022)
The aim of this study was to evaluate the usefulness of the measurement of glucoseand serum fructosamine as possible indicative biomarkers for the diagnosis of caninediabetes mellitus (CDM). An analytical, descriptive, cross-sectional study was developedwith a sample of 30 canines from a shelter in Cundinamarca, Colombia. The animals werewithout clinical signs of CDM. Data on sex, breed, age, diet, reproductive history,symptoms related to CDM and vaccination status of each animal were taken. A samplewas collected from the cephalic vein while fasting for 8-12 hours and were immediatelycentrifuged to determine the concentration of glucose and serum fructosamine in anautomated chemistry equipment. The results showed that 60% of the sampled populationwas male, 46.7% was 5 years old, 33.3% between 6 and 10 years old, and 20% more than10 years old. All were consuming an exclusive diet of concentrate and all were sterilized.The results showed that 30% of canines without clinical signs of CMD presented higherglucose concentrations and fructosamine concentrations below the established biologicalreference interval.